(3egGQGJ GdJahb GdOQGSjs - (3GdefRdGhj, CMeOs ((3GdbGgQIs (3GdafGQs, 2023)
(3GdESdGe ceG Cfg jgJe HhLhO Gdabjg GdeSde(B, (3cPdc jgJe HhLhO GdWHjH GdeSde hGdegfOS GdeSde hGdYGed GdeSde, Hd EPnG GMJGL GdeSdehf aj ecGf eG Edi WHjH eKkdG hde jcf Hjfge Pdc GdWHjH CKehG LejkYG, hdG jRGd GdeQHhf hGdOYGI hGdeUdMhf jPcQhf GdWdHI HCgejI GdJahb GdOQGSj ddaQO hGdCSQI hGdeLJeY hGdCnqeI, dcf gPg GdbVjI GdTGFcI df jLOj ajgG GdMeGSI hGdJfXjQ hGSJKGQI GdYGWaI aMSH, dG HO EPf ef efgL Yedj, hHQfGeL EQTGOj, hJhLjg GdWdGH dCbUQ GdWQb hCSgd GdWQGFb, dJMbjb gPG GdJahb(B. (3haj gPG GdcJGH CbOe YTQ egGQGJ jMJGL EdjgG cd WGdH, djMbb GdJahb GdOQGSj GdPj fSYi Edjg, cd egGQI dgG HQfGeLgG hNWhGJgG MJi jJjSQ ddWdHI GdSjQ YdjgGs
Keywords: (3GdJYdjes -- (3eUQs; (3GdfLGMs